Razlike v dosežkih iz matematike v raziskavi PISA glede na spol, izobraževalni program in status priseljenca - Šterman Ivančič, Klaudija (Matematika v šoli, 2023)
This paper examines the mathematics performance of Slovenian 15-year-olds in the PISA survey, focusing not only on the average performance but also on disparities in performance by gender, educational programme and immigration status. For this purpose, PISA samples from 2012 (n = 5911), 2015 (n = 6406) and 2018 (n = 6401) were used. Average mathematics achievement in PISA for Slovenia has been stable throughout and abo- ve the OECD average. However, the results of the analysis of differences in mathematics achievement between different groups of students show that in Slovenia, across all the survey data captures considered, there are no significant gender differences, but there are notable differences in mathematics achievement by educational programme and immigrant status, with the lowest scores among students attending vocational secondary education programmes and those reporting first-generation immigrant status. The results thus point to the need to further investigate the reasons for the achievement gap in mathematics, with a view to ensuring higher quality and equity in education.
Keywords: dosežki iz matematike; izobraževalni program; matematika; PISA; pismenost; spol; status priseljenca; vzgoja in izobraževanje